Deformations of Instanton Metrics - Bielawski, Roger; Borchard, Yannic; Cherkis, Sergey A. (Symmetry, Integrability and Geometry: Methods and Applications, 2023)
We discuss a class of bow varieties which can be viewed as Taub-NUT deformations of moduli spaces of instantons on noncommutative ℝ⁴. Via the generalized Legendre transform, we find the Kähler potential on each of these spaces.